CYBER CRIME PADA PRAKTEK JUDI BOLA ONLINE DI TANJUNGPINANG - Ferik Juanda; Siti Arieta; Nanik Rahmawati (JURNAL SOSIO-KOMUNIKA, 2024)
The purpose of this study is to find out how cyber crime is in the practice of online soccer gambling in Tanjungpinang. The object of this research is a coffee shop or kafe in the Bulit Bestari Village, Tanjungpinang City., the perpetrators' knowledge of cyber crime from online soccer gambling games. The results gambling carried out by informants is motivated by environmental factors of friendship, the existence of internet facilities that can support perpetrators to play online gambling freely. As well as the online soccer betting factor, it is confidential and easy to play anywhere and anytime. Informants know that playing online soccer gambling is a form of violation of the law. But they still do this because online gambling is difficult for the general public to detect. The behavior of cybercrime perpetrators of online soccer gambling starts from the process of communication and interaction that occurs in the social environment continuously. The sense of satisfaction and pleasure from playing soccer has made online soccer gambling even more desirable apart from the ease of accessing soccer gambling sites, which is very easy for anyone to do.